MEMBANGKITKAN MOTIVASI DAN SUPPORT PELATIHAN KERJA UNTUK MENINGKATKAN KINERJA - Sugeng Sismayadi; Bintang Narpati; Kardinah Indrianna Meutia; Dian Sudiantini; Wastam Wahyu Hidayat (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2023)
This study aims to determine the effect of the relationship between work motivation and training on employee performance. This research method uses a saturated sample to determine respondents from a population of 134 employees. To obtain data is carried out by interviews, observations and distribution of questionnaires to the leaders and employees of the company. In addition, secondary data is also carried out by taking theories in previous articles or journals and literature studies. Encouragement Work motivation is needed by employees to develop their careers by attending trainings provided by company management. The role of leadership is needed in supporting the training of employees. Therefore, leaders should provide opportunities for employees to develop their careers and abilities to be more expert in their fields, besides that work motivation from leaders is important to raise enthusiasm in employees. To determine the magnitude of the influence of each independent variable, namely work motivation and training on the dependent variable or employee performance. Multiple linear regression analysis techniques were used in this study.